Force : animal drawing : animal locomotion and design concepts for animators - Mattesi, Michael D. (Waltham, MA : Focal Press, 2011)
Provides instructions on the techniques of drawing a variety of animals using the basics of animal locomotion and anatomy.
Includes bibliographical references (p. 189) and index.
Keywords: Animals in art; Motion in art; Drawing -- Technique